Featured Cover. Issue 11 (2nd November 2022) - Zhu, Mengyuan; Fan, Zhipeng
Abstract : The cover image is based on the Review The role of the Wnt signalling pathway in the energy metabolism of bone remodelling by Mengyuan Zhu and Zhipeng Fan https://doi.org/10.1111/cpr.13309 .